Length–weight relationships of three freshwater fish species from Rupnaryan and Kangsabati River, West Bengal, India. (22nd October 2018) - Chini, Deep S.; Bhattacharya, Manojit; Kar, Avijit; Malick, Ramesh C.; Patra, Bidhan C.; Patra, Shampa; Das, Basanta K.
Abstract: The length–weight relationships (LWRs) of three freshwater fish species from the Kangsabati and Rupnaryan river in West Bengal, India are presented, namely as Amblypharyngodon microlepis (Bleeker, 1853), Parambassis lala (Hamilton, 1822) and Macrognathus aculeatus (Bloch, 1786). Gill‐nets (mesh sizes with 0.5 cm–4 cm), cast‐nets (up to 1 × 1 cm mesh size with up to 4.0 m 2 area) and scoop‐nets (0.3 × 0.3 cm and 0.5 × 0.5 cm mesh size) were used from January, 2017 to April, 2018. Sampling was done every 15 days during this period. The value of parameter "b" ranged from 2.751 to 2.895 with highly significant correlations ( r 2 > 0.95).